2016
DOI: 10.1159/000447809
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Protects Myocardium Against Ischemia-Reperfusion Injury Through Inhibiting miR-199a-5p

Abstract: Objective: This study aimed to evaluate the protective effects of atorvastatin against myocardial ischemia/reperfusion (I/R) injury in cardiomyocytes and its possible underlying mechanism. Method: Direct cytotoxic effect of OGD/R on cardiomyocytes with and without atorvastatin pretreatment was evaluated. Effects of atorvastatin on expression of GSK-3β and miR-199a-5p were determined using RT-PCR and Western blot. In addition, GSK-3β expression with miR-199a-5p upregulation and downregulation was detected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 32 publications
3
42
0
Order By: Relevance
“…Accumulating evidence indicates that miRNAs play key roles in MIRI, including inflammation, apoptosis, and angiogenesis [15][16][17][18][19][20]. In 2009, Wang and colleagues reported that MiR-327 expression levels were up-regulated in type-2 diabetic rat models using a miRNA microarray [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that miRNAs play key roles in MIRI, including inflammation, apoptosis, and angiogenesis [15][16][17][18][19][20]. In 2009, Wang and colleagues reported that MiR-327 expression levels were up-regulated in type-2 diabetic rat models using a miRNA microarray [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that miRNAs play an essential role in MIRI [15][16][17][18][19][20]. For example, miR-199a-5p, miR-15, and miR-92a aggravate MIRI, while miR-17-3p, miR-210, and miR-499 are cardioprotective miRNAs [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on reducing the time of hypoperfusion to preserve organ function. For sepsis, the Surviving Sepsis Campaign guidelines recommend early goal-directed therapy for timely resuscitation, including early antibiotic treatment and resuscitation with adequate fluids and vasopressors to reduce peripheral tissue hypoperfusion [1-8]. For acute coronary syndrome, the ACCF/AHA/SCAI guidelines recommend early revascularization to control myocardial injury [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that a single miRNA can influence multiple gene transcripts to regulate the complex process of gene expression, ultimately affecting the physiology of a cell [5]. Hence, miRNAs have been regarded as main regulators in almost all cellular processes, including differentiation, proliferation, necrosis and apoptosis [7,8]. Zhu WS et al investigated the role of miR-1 in I/R-induced injury and found that the suppression of miR-1 might be protective against myocardial I/R injury [9].…”
Section: Introductionmentioning
confidence: 99%